Learn AWS Cloudshell - Deza, Alfredo (Pragmatic AI Solutions, 2021)
Learn to use AWS Cloud Shell to master the AWS ecosystem. In this tutorial the following techniques are covered: Bash, ZSH, Powershell, S3, Lambda, Python, IPython, Pip, Boto3, DynamoDB and Cloud9.